Analysis of changing Recruitment Trends Based on Client Preferences - Thirupathi, T; Kanimozhi, V (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
The recruitment landscape has undergone a significant transformation in recent years, driven by changing client preferences, rapid technological advancements, and evolving workforce dynamics. This study aims to explore these shifts, with a particular focus on the trends affecting professional recruitment agencies and HR departments across key sectors like IT, healthcare, and finance. Using a mixed-methods approach, the research gathered insights from 173 industry professionals through structured questionnaires, highlighting key factors influencing hiring strategies. The findings reveal a growing emphasis on flexibility in hiring models, with project-based, bulk, and internship/graduate program hiring emerging as dominant practices. Technological integration, especially the use of artificial intelligence (AI) and automation, has also become central to modern recruitment, enhancing efficiency and reducing bias. Additionally, the importance of soft skills, diversity, equity, and inclusion (DEI) has grown, reflecting a broader shift toward more consultative, partnership-based recruitment services. The study concludes that recruitment firms must adapt to these changing dynamics by adopting flexible models, investing in technology, and aligning closely with client needs to remain competitive.